Estudo comparativo das tensões e microdeformações ao redor de pilares protéticos microunit e ucla sob carregamento axial estático - Santis, Leandro Ruivo de [UNESP] (2015)
The aim of this in vitro study was to compare microstrain and stress development around implants during axial loading, varying abutment type and load application point, using strain gauge and photoelastic analysis. Two polyurethane blocks were made, being inserted three external hexagon implants each. Microunit abutments were screwed on the first block and UCLA abutments were screwed on the second block. The respective plastic copings were installed onto the microunit abutments. The plastic copings and UCLA abutments were adapted to a standard resin pattern and cast in Ni-Cr alloy. The blocks were replicated in photoelastic resin. The metallic structures were screwed into the microunit abutments and into the implant plataform, respectively. The photoelastic blocks were submitted to a static vertical 7,5 kgf load using a load application device adapted on polariscope. Four strain gauges were bonded to the surface of each polyurethane block, tangetially to each implant. A static vertical 30 kgf load was applied for 10 seconds, using a load application device on points A, B and C. The data were analyzed by two-way RM ANOVA and Sidak's post hoc test (p< 0.05). Ucla abutments showed lower microstrain mean values (597,8 με) when compared to microunit abutments (988,3 με). The abutment factor was statistically significant (p<0.0001), load application point wasn't statistically significant (p=0,9437). UCLA system showed similar stress distribution patterns to conventional abutments. The pattern of stress distribution was different at point B. In conclusion, the presence of conventional prosthetic pillar interfered in stress distribution and microstrain development